Why Anesthesia? A national survey of the 1st year Anesthesiology trainees at Portugal. - Correia, André; Mendes-Castro, Alfredo (Journal of the Portuguese Society of Anesthesiology, 2022)
Introduction: Medical career choice is a complex process. Anesthesiology seems to be an interesting medical career in Portugal. However, the factors associated are unknown. We aimed to identify and explore the motivational factors involved in Anesthesiology career choice. Materials and methods: We performed a cross-sectional study. An electronic survey regarding motivation to choose Anesthesiology was developed. Motivation was measured using a 5-point Likert scale where reasons to choose Anesthesiology were classified between “nothing” and “extremely preponderant”. The survey was applied by email to all the anesthesiology trainees attending the first internship year in Portugal during 2021(N=80). Statistical analysis was performed using descriptive statistics and Chi-square test. Results: The response rate was 82,5%. Sixty-three percent were female. Median age was 26 years old. Seventy-seven percent had previous contact with Anesthesiology during pre-graduated education and was the first option from 86,4% of residents. Virtually all would choose the same option again. When considering the most preponderant motivation to choose Anesthesiology, the following factors were classified as “very and extremely preponderant” by more than 50% of respondents: transversality, hands-on specialty, adaptation to personal characteristics, perceived job satisfaction, employability, work/life balance, emergency and critical care, financial perspectives, physiology and pharmacology, predominant operative room workload, low ward workload and career perspectives. Discussion and Conclusion: Personal factors and transversality of the specialty seems to be relevant factors associated with Anesthesiology career choice. Further studies should be applied on an annual basis and emphasize how the motivational factors differ between different specialties.